A split motor domain in a cytoplasmic dynein - Straube, Anne (Oxford University Press, 2001)
The heavy chain of dynein forms a globular motor domain that tightly couples the ATP-cleavage region and the microtubule-binding site to transform chemical energy into motion along the cytoskeleton. Here we show that, in the fungus Ustilago maydis, two genes, dyn1 and dyn2, encode the dynein heavy chain. The putative ATPase region is provided by dyn1, while dyn2 includes the predicted microtubule-binding site. Both genes are located on different chromosomes, are transcribed into independent mRNAs and are translated into separate polypeptides. Both Dyn1 and Dyn2 co-immunoprecipitated and co-localized within growing cells, and Dyn1–Dyn2 fusion proteins partially rescued mutant phenotypes, suggesting that both polypeptides interact to form a complex. In cell extracts the Dyn1–Dyn2 complex dissociated, and microtubule affinity purification indicated that Dyn1 or associated polypeptides bind microtubules independently of Dyn2. Both Dyn1 and Dyn2 were essential for cell survival, and conditional mutants revealed a common role in nuclear migration, cell morphogenesis and microtubule organization, indicating that the Dyn1–Dyn2 complex serves multiple cellular functions.